Scanning torsional-flexural frequencies of thin-walled box girders with rough surface from vehicles' residual contact response: Theoretical study. (December 2021) - Yang, Y.B.; Mo, X.Q.; Shi, K.; Wang, Zhi-Lu; Xu, Hao; Wu, Y.T.
Abstract: This paper studies theoretically the retrieval of torsional-flexural frequencies of mono-symmetric thin-walled box girder bridges from vehicles' residual contact response for the first time. To start, the three-dimensional vehicle–bridgeequations of motion including the lateral and torsional (coupled) and vertical (uncoupled) vibrations are derived for a moving test vehicle. Then, closed-form solutions for the vehicle and vehicle–bridge contact point are derived. The contact response is selected since it is free of vehicle frequency, which may overshadow the bridge frequencies in FFT spectra. The other disturbing factor is surface roughness, which will be resolved by the residue method, i.e., by using the residual response of two connected vehicles. Through the parametric study, the proposed approach is verified to be feasible. The conclusions include: (1) the contact response performs better than the vehicle response for all the scenarios considered; (2) the surface roughness effect can be virtually eliminated using the residual contact response even for damped bridges with not-so-good pavements; (3) a larger vehicle's eccentricity from bridge's centerline enables the torsional-flexural frequencies to be better identified; and (4) the first several flexural and torsional-flexural frequencies of the girder can always be identified for a wide variety of parameters considered. Highlights: Scan newly 3D beam's torsional-flexural frequencies from vehicles' contact residue. Derive new closed-form solutions for the vehicle and vehicle–bridge contact point. Eliminate surface roughness using residual contact response of connected vehicles. Identify first few torsional-flexural frequencies for a wide variety of parameters. Parameters studied: roughness, bridge damping, vehicle's eccentricity, moving speed.